Disabling fun : The connection of the bodily and mentally disabled and the profession of fool under the consideration of the benign violation theory of humour - Meyer-Küpers , Jonathan S. (Peripeti, 2025)
This paper examines the Benign Violation Theory of Humour (BVT) in relation to disabled individuals in the professions of historical fools and jesters. It explores how cultural and historical contexts have shaped their employment and impact on modern performances. Finally, it analyses how shifts in thinking influence the perception of humour in these performances. Denne artikel undersøger the Benign Violation Theory of Humour (BVT) i forhold til handicappede personer i erhvervet som historiske narre. Den undersøger, hvordan kulturelle og historiske kontekster har formet deres beskæftigelse, og hvilken indflydelse det har på moderne forestillinger. Endelig analyseres det, hvordan ændringer i tankegangen påvirker opfattelsen af humor i disse forestillinger.